Exploring the Organized Realities and Education Logics In the Qualification Training System for Level 2-Sport-for-all-Coach Through the Analysis of Coordination Process - Juyoung Ryou (Korea Institute of Sport Science, 2021)
Purpose There are two purposes of this study; First is to investigate the reality of curriculum in the qualification system through the coordination process between participants' experiences and institutional texts. Second is to identify the light and shade of the educational logics underlying the certificate courses of Level 2-sport-for-all-coach. Methods By relying on the institutional ethnography approach(Smith, 2005), the data were collected through on-site materials and semi-structural interviews with seven coaches who participated in the qualification programmes after 2015 system revision. The data were analyzed by mapping the social organization. Results The analysis shows two key findings. First, participants faced inconsistencies with institutional texts in the subcategories of qualification system and experienced (self-)rationalization process including doubt, complaint, acceptance and compromise toward the system. Second, Performance pedagogy and Craft pedagogy were operating at the root of the current qualification system, and the two logics led to the fundamental limitations(unlinked educational content, passive educational activity, and unsystematic educational operation) for the improvement of system. Conclusion The activation of the retrospective approach to distinguish the pros and cons of various educational logics was suggested. These findings are expected to provide useful implications for building the future framework to educate sport-coaches more systematically.